Important elements for good territorial public governance focused on sustainable local development - Almeida, Thiago Chagas de; Emmendoerfer, Magnus Luiz (GOT: Revista de Geografia e Ordenamento do Território, 2026)
Research Purpose: Sustainable Local Development (SLD) is an endogenous process – based on the resources and needs of the territory – that aims to improve the quality of life of society by balancing several territorial factors. Despite the potential benefits of SLD, it is not something random, but requires the coordination and appropriate direction of the efforts of territorial actors, that is, good territorial public governance. Based on this issue, this study aims to identify the fundamental elements for good territorial public governance focused on SLD. Methodology: The research was conducted through an integrative literature review, focusing on open access articles available in the Scopus and Web of Science databases. The data were interpreted using thematic content analysis, creating categories associated with the purpose of this study. Findings: The results indicate that the main attributes of good territorial governance for SLD are: access to governance mechanisms; engagement of local stakeholders in governance; local representativeness in governance; transparency of governance actions; governance sustainable responsibility; and effectiveness of governance. Originality/Value: This study contributes to a deeper understanding of the factors that qualify territorial public governance for SLD, offering practical benefits for territorial management while advancing the existing literature.